DOCÊNCIA NA EDUCAÇÃO INFANTIL: INTERSEÇÕES ENTRE VIVÊNCIAS DE ATUAÇÃO E DE FORMAÇÃO INICIAL - Giesen, Karina de Fatima (2020)
This research focuses on the teaching practice during the first stage of Brazilian basic education considering its intersection with the initial training in Pedagogy and by problematizing the context in which, given the expansion of assistance to young ch